Pengaruh Kualitas Pelayanan, Kulitas Produk, Harga, dan Kepercayaan Konsumen Terhadap Kepuasan Konsumen Roti Sajiyem - Putri, Dyah Sancaya; Kusnandar, Kusnandar; Khomah, Isti (Universitas Galuh, 2025)
Small and Medium Enterprise (SME) have an important role in the Indonesian economy, including Roti Sajiyem which has been operating since 1998. Roti Sajiyem customer satisfaction is influenced by product quality, service, price, and trust. This study aims to analyze the influence of service quality, product quality, and price on consumer trust and satisfaction, as well as to test the role of trust in consumer satisfaction. Sampling was conducted using the accidental sampling method with 100 respondents, data was collected through questionnaires and analyzed using Structural Equation Modeling-Partial Least Square (SEM-PLS). The results showed that product quality had a significant effect on consumer satisfaction, while service quality and price had no significant effect. Service quality, product quality, and price have a positive and significant effect on consumer confidence. To increase satisfaction, Roti Sajiyem needs to maintain consistency in product quality through clear Standard Operating Procedures (SOP), improve service quality, and ensure prices are proportional to quality to strengthen consumer trust and satisfaction.